Pemberdayaan Siswa Melalui Pembelajaran Tari dan Aksesori Kertas Bulu Enggang di SMPN 5 Bontang: Pengabdian - Astri Juwita Fardhani; Yofi Irvan Vivian; Fatimah M; Nofriyan Hidayatulloh; Ade Febri Yulfita; Chornelia Ajis (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This community service program aims to enhance students’ creativity and understanding of dance arts through the creation of paper-based Kirip Bulu Enggang accessories as practical learning media, while also fostering appreciation for local culture. The program was carried out at SMP Negeri 5 Bontang involving students from grades VII, VIII, and X who are part of the school’s dance group. The methods included delivering material on the cultural values of the Bulu Enggang motif, demonstrating kirip-making techniques, guiding students through hands-on practice, and providing supervision and evaluation of their work. Throughout the activity, students developed fine motor skills, visual creativity, and the ability to express dance movements using the accessories they created. The results showed increased enthusiasm and participation, reflected in their active involvement and ability to produce neat, wearable kirip pieces. Overall, the program strengthened cultural pride and provided a more practical and meaningful learning experience in dance arts.